APPROACHES TO ASSESSING THE STATE OF HUMAN CAPITAL IN THE COUNTRY - Kim Elena Radionovna (Labor economics and human capital, 2025)
The scientific community has long debated the drivers of economic growth and its key determinants. Among the most critical factors explaining differences in prosperity levels between nations, human capital occupies a central position – defined as the aggregate of a population's knowledge, health, competencies, and professional skills. In modern economies, human capital has become the primary driver of innovation-led economic growth. Consequently, the fundamental challenge facing every nation is building high-quality human capital. This article is devoted to the analysis of the most common approaches to the implementation of a comprehensive assessment of the degree of human capital development in the country.